Peran Keluarga dalam Pertumbuhan Gereja di Era Digital - Nunuk Novianti; Sang Putra Immanuel Duha (Jurnal Arrabona, 2023)
In the digital era like today, which is marked by the birth of various innovations and technologies, of course, it is very influential for the growth of a church and the role of a family. The influence of the digital era also affects a family, especially Christian families. The researcher conducted an analysis with a literature review from relevant sources found in previous studies as well as literature, books and other reference sources in digital media. All of these sources are analyzed by looking at the relationship, relevance and suitability of the title of this research, namely the Role of the Family in the growth of the church in the digital era. The results obtained can then be used as a family concept so that it has a positive impact on church growth in the digital era.